Effect of soaking seeds Citrusaurantium and Citrus limonumat different concentrations of licorice extract on the percentage of germination and growth of seedlings (Baghdad Science Journal, 2016)
This research was conducted under Lath house canopy of a nursery circumstances, Baghdad University for season 2013 in order to study the effect of soak lemon seeds sour orange with different levels of licorice concentrations extract (0, 0.5, 2.5 and 4.5 g/l) for 24 hours in the percentage of germination and some recipes vegetative growth of seedlings .the results outweigh the bitter orange seedlings and focus soak for licorice extract 4.5 g / l significant superiority in most of the traits plant height, leaf number, root length, stem diameter, amounting to 31.077 cm, 14.46 paper / plant, 25.35 cm, 0.52 mm respectively, which showed significant differences for the treatment of comparison which gave lower values. Clear that the licorice extract biological effect similar to the effect of Al Gibberellin at germination lemon seeds, sour orange.